Effectiveness of Sesame Seeds Cookies (Sesamum Indicum Seeds) Combination of Iron In Increasing Hemoglobine Levels Of Adolescents - Tangko, Yuliani; Suwondo, Ari; Supriyana, Supriyana (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Female adolescent anemia is a health problem in Indonesia. Iron has not been able to reduce anemia. One of the causes is because people are not obedient in consuming Fe tablets. Sesame seeds are a plant-based source of iron which has no side effects and is a potential iron supplement in treating anemia. The research design was a pretest-post test quasy experiment with a control group design with a purposive sampling technique. The sample consisted of 42 people who were divided into 2. Data analysis used independent test, paired test, Mann Whitney test and Wilcoxon sign rank test. The combination of 91 mg sesame meal with Fe tablet was proven to increase hemoglobin levels p value = 0.013 <0.05. Sesame seeds contain various important nutrients, namely iron, folate, flavonoids, copper and other nutrients that play a role in increasing hemoglobin levels so that they can overcome anemia.